2020
DOI: 10.3389/fgene.2020.00058
|View full text |Cite
|
Sign up to set email alerts
|

Association of BLK and BANK1 Polymorphisms and Interactions With Rheumatoid Arthritis in a Latin-American Population

Abstract: Introduction: BLK has been identified as a risk factor to rheumatoid arthritis (RA) primarily in Asian or European-derived populations. However, this finding has not been evaluated in other populations such as Latin-Americans, except for Colombians. On the other hand, BANK1 single nucleotide variants (SNVs) have been scarcely studied in RA patients. Objective: The aim of this study was to determine whether the BLK rs2736340T/C, rs13277113A/G, and BANK1 rs10516487G/A (R61H) and rs3733197G/A (A383T) polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In the last decade, several studies have shown that the analysis of gene–gene interactions between different genes plays an important role in the risk of developing complex diseases such as coronary heart disease, rheumatoid arthritis, and hyperlipidemia [ 26 , 27 , 28 , 29 ]. In this study, we evaluated whether the gene–gene interaction between BAT1 rs2239527 C / G , NFKBIL1 rs2071592 T / A , LTA rs1800683 G / A , CASP1 rs580253 A / G, and CASP1 rs501192 A / G polymorphisms could be jointly associated with the risk of developing restenosis after stenting using the multifactor dimensionality reduction (MDR) program.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, several studies have shown that the analysis of gene–gene interactions between different genes plays an important role in the risk of developing complex diseases such as coronary heart disease, rheumatoid arthritis, and hyperlipidemia [ 26 , 27 , 28 , 29 ]. In this study, we evaluated whether the gene–gene interaction between BAT1 rs2239527 C / G , NFKBIL1 rs2071592 T / A , LTA rs1800683 G / A , CASP1 rs580253 A / G, and CASP1 rs501192 A / G polymorphisms could be jointly associated with the risk of developing restenosis after stenting using the multifactor dimensionality reduction (MDR) program.…”
Section: Discussionmentioning
confidence: 99%
“…Three polymorphisms within CD40 (rs1883832, rs1535045 and rs4813003) and BLK (rs2254546, rs2736340, rs2618476) genes as well as two genetic variants within BANK1 (rs10516487 and rs3733197) were selected in this study. These eight specific variants were selected considering that they were related to numerous inflammatory disorders [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In addition, potential functional consequences were previously proposed for some of these polymorphisms [ 8 , 18 , 19 , 36 ].…”
Section: Materials and Methodologymentioning
confidence: 99%
“…In this regard, BLK is a src family nonreceptor tyrosine kinase [ 5 ] with a relevant role in the development and receptor signaling of B-cells [ 6 ], whereas BANK1 is an adaptor/scaffold that participates in B-cell activation and signalization [ 7 , 8 ]. Interestingly, CD40 [ 9 , 10 , 11 , 12 , 13 ], BLK [ 7 , 14 , 15 , 16 , 17 , 18 ] and BANK1 [ 7 , 8 , 18 , 19 ] genes are identified as susceptibility loci for several inflammatory diseases. Likewise, CD40 and BLK variants are known as susceptibility factors for different forms of vasculitis, specifically for the development of ischemic manifestations in patients with giant cell arteritis [ 20 , 21 ] and for Kawasaki disease [ 13 , 22 ], supporting the relevance of B-cell activation in the pathophysiology of both vasculitides.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 Furthermore, BLK is involved in the immune tolerance of B lymphocytes, affecting the function of B cells, which may lead to autoreactive or regulatory cellular responses, increasing the risk of autoimmune diseases. Most studies have provided reliable evidence that the single nucleotide polymorphisms (SNPs) of BLK exert a key role in susceptibility to various autoimmune disorders, such as SLE, 15 rheumatoid arthritis (RA), 16 SS, 17 thyroid disorders, 18 and systemic sclerosis. 19 Similarly, NMOSD is also mainly a B cell‐mediated autoimmune disease.…”
Section: Introductionmentioning
confidence: 99%